H Hubungan Prehospital Delay Dengan Tingkat Keparahan Pada Pasien Stroke Di Rumah Sakit Banjarmasin - Solikin; Muhammad Firdaus; Julianto Julianto (Journal of Nursing Invention, 2022)
Background: Stroke patients need golden time in treatment Â±3 hours which means that in the first 3 hours after having a stroke the patient must get complete and optimal care. Objective: To determine the relationship between prehospital delay and severity in stroke patients in Banjarmasin city hospitals. Method: This research is a quantitative study using a correlational descriptive research design with a retrospective approach. Sampling was carried out using purposive sampling techniques, the sample in this study was 124 respondents. Data collection using prehospital observation of stroke patients with Spearman Rank statistical test. Results: The results of statistical tests in this study obtained a p-value of 0.000 < 0.05 and it can be stated that there is a significant relationship between prehospital delay and the severity of stroke patients at Banjarmasin City Hospital. The relationship between these two variables indicates in the direction of a negative correlation with the Spearman Rank value - 0.948 which means that the relationship between the two variables has perfect relationship. Conclusion: There is a significant relationship between prehospital delay and the severity of stroke patients at Banjarmasin City Hospital.